The most efficient level of winter protein feeding for yearling steers wintered and summer razed on bluestem pasture. - Smith, E.F.; Baker, F.H.; Cox, R.F.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
Twenty head of good quality Hereford yearling steers were used in this study. They were purchased from the Brite Ranch at Marfa, Texas, in the fall of 1952 as calves for 28 cents a pound. They were used in summer grazing tests on bluestem pasture in 1953. '1'hi8 test started at the close of the summer grazing season on October 26, 1953, and extended to April 1, 1954. During this test the steers were moved from pasture to pasture every 15 days to minimize any differences due to pastures. . During March one-half of the steers• in each lot had access to molasses-sprayed grass in a pilot test to find out if this method of feeding- might have some .possibilities. The pastures in which the steers were grazed were of such size as to vary the stocking rate from 6 to 19 acres per head. All pastures used in this winter test had sufficient grass remaining for winter use. They were lightly stocked during the summer of 1952.
Keywords: Beef; Protein; Yearlings; Bluestem pasture; Gain